Implications of ROEs Legal Form on Company Management - Hasan, Miftahol (Jurnal Hukum Indonesia, 2025)
This research examines the implications of the legal forms of Regional-Owned Enterprises (ROEs, known as BUMD or Badan Usaha Milik Daerah) on company management. In the Indonesian context, ROEs typically take the form of either Regional Companies (known as PD, or Perusahaan Daerah) or Limited Liability Companies (LLC, known as PT, or Perseroan Terbatas), which are regulated under Law No. 23 of 2014 and PP No. 54 of 2017. The legal form of an ROE significantly influences its organizational structure, operational efficiency, accountability, and sustainability. ROEs structured as LLCs tend to excel in management flexibility and access to funding, while PDs are more focused on delivering public services. However, both legal forms face distinct challenges, such as political interference in PDs and conflicts between commercial and social objectives in LLCs. This research recommends the implementation of Good Corporate Governance (GCG) principles to enhance the efficiency and accountability of ROEs. By understanding the implications of the legal form, local governments can better optimize the role of ROEs in supporting economic development and community services.